EU och den nationella regleringen av cannabis - En jämförande rättslig analys av Tysklands och Nederländernas modeller i förhållande till unionsrätten - Lazovic,Luka (2025)
This thesis examines the compatibility of Germany’s and the Netherlands’ national cannabis legalization models with the EU rules on the free movement of goods, particularly Articles 34–36 of the TFEU. The purpose is to assess the extent to which these national regulations align with EU law and to identify potential legal risks and opportunities. A combination of legal dogmatic and EU-legal methodology is applied, with analysis based on CJEU case law, such as Cassis de Dijon, Dassonville, and Josemans. Germany’s model is structured around non-commercial cultivation associations and strictly regulated private use, while the Netherlands employs a tolerance policy allowing retail sales in coffeeshops for their citizens. The thesis concludes that Germany’s reform, especially its first implementation phase, is likely compatible with EU law, whereas the Dutch model occupies a more legally ambiguous position. The status of cannabis as a legally circulated good in the EU remains uncertain and subject to evolving case law and policy interpretation.
Keywords: EU-rätt; Fri rörlighet av varor; Cannabis; Tyskland; Nederländerna; Folkhälsa; Proportionalitet